Incidence and prevalence of paediatric home parenteral nutrition (HPN): a nationwide study from the Scottish HPN managed clinical network. (13th March 2011) - Barclay, A R; Baxter, J; Wilson, D C
Abstract : Introduction: The four tertiary centres in Scotland providing paediatric (<16 years of age) HPN are formalised within the Scottish HPN MCN; only these centres have facilities and expertise to give prolonged PN beyond term. Scotland comprises 8.6% (5.2 million/61 million × 100) of the paediatric population of the UK. Our aim was to demonstrate nationwide incidence and prevalence of need for paediatric HPN in Scotland, as a representative part of the UK. Methods: The prospective cohort of HPN cases managed in all 4 tertiary paediatric HPN centres in Scotland (Aberdeen, Dundee, Edinburgh and Glasgow) has been ongoing from 01/2003. We reviewed prevalence and incidence of paediatric HPN for each year from 2003 to 2010 (10 months only for 2010), with point prevalence on the 31 st of each October. Outcomes of interest included fate - continuing HPN or leaving paediatric network, and reason why. Results: There were 39 HPN cases in this period, with 6 prevalent cases on 01.01.03. There were 33 incident HPN, and 28 of 39 stopped HPN (14 adapted, 2 withdrew, 1 transitioned, 1 left Scotland, and 10 died). Prevalence and incidence data are shown in table 1 . * 01.01.03-31.10.10 only. Conclusion: We report nationwide data on the incidence and prevalence of paediatric HPN in Scotland, managed in the 4 HPN centres. Extrapolation of our Scottish nationwide data (collected within a national MCN) to the UK ((nx100/8.6)/12 years) suggests that there are annual minimum paediatric incidences and period prevalences of 48 and 126 cases respectively needing HPN in the UK, with an increasing trend in the last 8 years. These data are important for counselling families and for planning regional and national paediatric HPN specialist services in the UK.